KAJIAN FONOLOGI BAHASA BANJAR DI KAMPUNG PARIT TABOR - NUR AFIQAH, AZEMAN (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study was conducted to study the phonological system of the Banjar language that is spoken in Batu Pahat, Johor. This study focuses on Banjar language in Batu Pahat, Johor which is not given much attention. The objective of this study is to identify the vowel and consonant phonemes that exist in Banjar language, the diphthongs that exist in Banjar language and the vowel clusters that exist in Banjar language. the researcher has applied the Asmah’s Descriptive Model (2006) to analyze the data. The data of this study was obtained through upstream field study using the Swadesh list as well as experiences that are not forgotten by the informants. Descriptive analysis was used to determine the six (6) vowel sounds and 19 consonant phonemes as well as diphthongs and vowel clusters that exist in Banjar language. Diphthongs in Banjar language consist of four types which are diphthongs /au/, /uy/, /ay/ and /oy/. Meanwhile, the vowel clusters in Banjar language have been divided into two types which are the front vowel clusters and the back vowel clusters. The front vowel clusters consist of five types which are /ia/, /ia/, /ua/, /aa/ and /ii/, while the back vowel clusters consists of only one type which is /au/.